ترقي استيعاب المفردات العربية وتأثير طريقة الاستجابة الجسدية الكاملة لطلاب الفصل السابع بالمدرسة الإسلامية الشافعية المتوسطة - Ade, Ade Ruswatie; In'ami, Moh; Nafisah, Mawaddatun (Tarling : Journal of Language Education, 2023)
The objectives of this research 1) analyze the application of the T PR method; 2) looking at the influence of the TPR method on student learning outcomes; 3) knowing the advantages of the TPR method from conventional methods. This field research uses a quantitative approach (Pre-Exsperimental research design in the form of Quasi Experimental Design the non equivalent control group design). Its objects are class VII A (experimental class) and class VII B (control class). Data collection techniques are tests and observations. Adata analysis with a two-way One Sample T-test t test to determine the influence of the TPR method on the experimental class and the N-Gain test for a comparative test of the learning outcomes of the TPR method and conventional methods. The results of the One Sample T-test obtained t count 25,729 so that it is greater than ttable 2.201 and sig values. (2 –tailed) which is 0.000 < 0.05, which means that the TPR method is effective. And based on the N-Gain test, it was obtained that the score for the experimental class was 76.9410 or 76.94% (effective category), and the average N-Gain score for the control class was 60.5605 or 60.1% (quite effective). Inconclusion, the TPR method is better than conventional methods for student learning outcomes in improving mastery of muphrodat.